APLIKASI RHIZOBIUM DAN CENDAWAN MIKORIZA ARBUSCULA (CMA) TERHADAP PERTUMBUHAN TANAMAN KACANG TANAH (Arachis hypogeal) DI DESA SOCAH KECAMATAN SOCAH KABUPATEN BANGKALAN MADURA - Tutik Nurhidayati; Nurul Jadid; Safita Meridian (The East Java Biological Society, 2011)
The cultivation of peanuts in Socah village mostly located in marginal land. On the other hand to increase the productivity of land by local communities is use of chemical fertilizers. The effects of chemical fertilizers is the decline in the productivity of the land. In these circumstances it is absolutely necessary to perfect technology of dry land resources is essential. One of the technologies that can be developed is the use of rhizobium and mycorrhiza. Thus occurred the tripartite relationship between rhizobium, mycorrhiza, and plants arbuscula beneficial for growth and development of land. In this study the application of local rhizobium and mycorrhiza on crops of peanuts, with measurable parameters of nodule formation and detection of plant growth and productivity of peanut.